Association between serum vitamin B6 concentration and risk of osteoporosis in the middle-aged and older people in China: a cross-sectional study. Issue 7 (4th July 2019) - Wang, Jing; Chen, Lin; Zhang, Yan; Li, Chen-guang; Zhang, Hao; Wang, Qiang; Qi, Xiaofeng; Qiao, Liang; Da, Wei-wei; Cui, Xue-jun; Lu, Sheng; Wang, Yong-jun; et al.
Abstract : Objective: To determine the relationship between serum vitamin B6 (Vit B6 ) concentration and the status of bone mineral density and identify the relationship between serum Vit B6 and bone metabolism parameters in middle-aged and older people in China. Design: The present study was a cross-sectional study within the framework of an ongoing prospective population-based cohort study. Setting and participants: A total of 1829 residents (men ≥50 years and women ≥45 years) from two subdistricts were recruited from July 2015 to February 2016 in Shanghai, China. Measures: Recruited residents were grouped (control, osteopenia and osteoporosis) according to their lumbar spine bone mineral density, measured through dual-energy X-ray absorptiometry. Serum Vit B6 concentrations, bone turnover marker concentrations and calcium and phosphorus metabolism parameters were assessed. Results: No significant linear trend between serum Vit B6 concentrations and lumbar bone mass was observed in the men. In the women, the average osteoporosis risk was 61% higher at serum Vit B6 concentrations of <19.2 μg/L than at those of >26.9 μg/L (OR 1.61, 95% CI 1.00 to 2.58). However, there was no significance after controlling of serum 25-hydroxy-vitamin D concentration and parathyroid hormone concentration, respectively. In the osteoporotic women, the serum Vit B6 concentration was significantly negatively correlated to concentrations of bone turnover marker including N-terminal propeptide of type I collagen, β-C-terminal telopeptide of type I collagen and osteocalcin. It was also positively related to the serum 25-hydroxy-vitamin D concentration and inversely related to the serum parathyroid hormone concentration. Conclusions: A relatively low serum Vit B6 concentration, even in the normal range, may be a risk factor for osteoporosis in postmenopausal women, which is dependent on serum 25-hydroxy-vitamin D concentration and parathyroid hormone concentration. Trial registration number: NCT02958020 ; Post-results.